Sustainable Property Business In The Area Of Delima Village, Tampan Sub-District, Pekanbaru City - Ibrahim, Mariaty; Musadad, Musadad; Fadli, Mashur (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study aimed to investigate the social, economic, and environmental impacts of housing construction in Delima Village, Tampan Sub-district, Pekanbaru City, using descriptive qualitative techniques and research subjects totaling twenty-one people. The data was collected through interviews and field observation. Interviews were done by asking questions directly to the research informants. Concerning social impacts, the study found social changes that formed new values as the implications of assimilating local values with external values. The mixed values were used as guidelines or foundations for the social interaction between the residents and newcomer residents. From the economic impacts, the housing construction created employment opportunities, increased the local people’s income, and improved their education and health levels. Regarding the environmental impacts, the local communities often experience difficulties obtaining clean water, reduced green and vacant land, less fertile soil, and test to get groundwater due to the loss of vegetation (trees). However, housing construction positively makes the environment around Delima Village more modern.